149k views
4 votes
H(x) = x^2 - 5x +7
Find h(-5)

2 Answers

5 votes

Answer:


\bold{h(-5)=57}

Explanation:

Substitute
-5 for everywhere there is
x


h(x) = x^2 - 5x +7\\=-5^2 - 5(-5) +7


-5^2 - 5(-5) +7

PEMDAS order of operations

Parenthesis


\bold{-5*(-5)}\\=25


-5^2+25 +7

Exponents


\bold{-5^2}\\=-5*-5\\=25


25+25 +7

Addition


25+25+7\\=50+7\\=57

Therefore,
\bold{h(-5)=57}.

User Pllumb
by
4.8k points
0 votes

Answer:

57

Explanation:

h(-5) = (-5)^2 - 5(-5) + 7

h(-5) = 25 + 25 +7

h(-5) = 57

User Rome
by
4.9k points